ANALISIS PENANGANAN IKAN PASCA-TANGKAP PADA KAPAL NELAYAN DI KARANGSONG, INDRAMAYU-JAWA BARAT - Junianto Junianto; Dede Nishfi Tamamul Lail (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
The freshness of the fish caught significantly influences its selling price. The level of freshness of the fish caught is influenced by the handling techniques employed by fishermen on board the vessel until the auction. This study aims to analyze the type of catch, onboard handling, and post-loading and unloading handling on small fishing vessels in Karangsong, Indramayu. The method used is a survey method. Data were obtained from interviews and field observations related to post-catch fish handling on small fishing vessels. The results showed that the type of fish caught by fishermen landed at the Karangsong PPI was mostly dominated by gray tuna. Handling on board the vessel begins with lifting the fish onto the vessel, washing, and storing it with ice in a cool box. The ice to fish ratio for short trips (<12 hours), they use an ice:fish ratio of 1:3 (w/w), while for long trips (>24 hours), the ratio is increased to 1:1.5 (w/w). The ambient temperature inside the cool box, while the ice cubes inside have not completely melted, is between 4 and 10°C. Post-loading and unloading handling includes unloading on land and collection by the TPI, transportation to cold storage, and delivery to collectors and middlemen.